Chapter Lo Spazio Europeo dell'Istruzione e la dimensione europea dell'insegnamento: profilo professionale e formazione del docente europeo - Marini , Antonietta (Studies on Adult Learning and Education, 2022)
According to the Maastricht Treaty, the responsibility for the organisation and content of education and training systems lies with the Member States. However, the Community contributes to the development of quality education and the European dimension of teaching by encouraging cooperation between Member States. Europeanisation of national education systems in the European Union is both the effect of a top-down political process, with different levels of governance, and the result of a bottom-up movement. The main agents are the teachers themselves: European mobility, both physical and virtual, improves their professional practice and helps to develop their sense of belonging to a European teaching and learning community. Despite the central role played by teachers in the integration of national education systems into the European Education Area, the profile and the key competencies of the 'European teacher' have not been defined in European Union policy documents.